2001
DOI: 10.1093/emboj/20.9.2120
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein VI but not alpha2beta1 integrin is essential for platelet interaction with collagen

Abstract: C.Brakebusch and W.Bergmeier contributed equally to this workPlatelet adhesion on and activation by components of the extracellular matrix are crucial to arrest posttraumatic bleeding, but can also harm tissue by occluding diseased vessels. Integrin a2b1 is thought to be essential for platelet adhesion to subendothelial collagens, facilitating subsequent interactions with the activating platelet collagen receptor, glycoprotein VI (GPVI). Here we show that Cre/loxP-mediated loss of b1 integrin on platelets has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

36
462
4
6

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 490 publications
(509 citation statements)
references
References 57 publications
36
462
4
6
Order By: Relevance
“…37,38 In this model, integrin ␣2␤1 is now thought to have a supportive, rather than a primary role as the adhesive collagen receptor, while GPVI is a major platelet-collagen activating receptor that interacts with collagen fibrils via a triplicate GPO sequence (glycine, proline, hydroxyproline) and integrin ␣2␤1 interacts with collagen via GFOFER (glycine, phenylalanine, hydroxyproline, glutamic acid and arginine). [39][40][41] For in vitro studies, we used CRP as the GPVI-selective agonist because this peptide contains 10 GPO repeat sequences and serves as a potent activator of GPVImediated signaling and does not recognize integrin ␣2␤1 . 42 In this way, we can differentiate GPVI-mediated platelet responses from integrin ␣2␤1-mediated platelet responses.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 In this model, integrin ␣2␤1 is now thought to have a supportive, rather than a primary role as the adhesive collagen receptor, while GPVI is a major platelet-collagen activating receptor that interacts with collagen fibrils via a triplicate GPO sequence (glycine, proline, hydroxyproline) and integrin ␣2␤1 interacts with collagen via GFOFER (glycine, phenylalanine, hydroxyproline, glutamic acid and arginine). [39][40][41] For in vitro studies, we used CRP as the GPVI-selective agonist because this peptide contains 10 GPO repeat sequences and serves as a potent activator of GPVImediated signaling and does not recognize integrin ␣2␤1 . 42 In this way, we can differentiate GPVI-mediated platelet responses from integrin ␣2␤1-mediated platelet responses.…”
Section: Discussionmentioning
confidence: 99%
“…There has been much debate regarding the roles of ␣ 2 ␤ 1 integrin and GPVI/FcR␥ complex in the two-step, two-site model (44,45). It has been suggested that engagement of GPVI may be required for activation of the ␣ 2 ␤ 1 integrin (29,44,45). We have previously shown that platelets from ␣ 2 ␤ 1 -deficient mice have delayed thrombus formation in vivo within the carotid artery (12), and that under flow conditions in vitro, GPVI/FcR␥ complex and ␣ 2 ␤ 1 integrin both play independent and vital roles in platelet adhesion and aggregation to collagen (46).…”
Section: Discussionmentioning
confidence: 99%
“…It also becomes activated through inside-out signaling by soluble agonists and by GPVI (27). The concept of a need for prior activation of ␣ 2 ␤ 1 for hemostatic function was furthered by murine studies, in which platelet adhesion was markedly attenuated by the absence of GPVI (8). Here, we show that although platelet binding to the lower affinity sequences does indeed require prior activation, binding to GFOGER (and to a lesser extent GLOGER) does not, which may allow platelets to interact with such sequence-containing collagens without a preceding switch in the integrin conformation.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the expression levels of ␣ 2 ␤ 1 have been associated with myocardial infarction and stroke (7). Recently, knockout studies suggested that the platelet activatory collagen receptor glycoprotein VI (GPVI) is mandatory for the initiation of integrin-mediated adhesion (8), but this concept was challenged by further mouse studies (9). Moreover, in vitro studies suggest that soluble collagen binding to ␣ 2 ␤ 1 requires a change in the conformation of the integrin (10).…”
mentioning
confidence: 99%